Desenvolvimento de metodologia para implementação de escritórios de projetos na administração pública municipal - Wilhelmsen, Rodrigo (Universidade do Vale do Rio dos Sinos, 2013)
The present work aims to develop the issue of implementing Project Offices, and culture of Project Management in Public Administrations, especially in small and medium-governmental structures. Justified this subject, before the public clamor for a more effective on the public management, and more forceful in achieving their goals and actions. Deserve special attention to small and medium Prefectures, simply because they represent about 90% of Brazilian municipalities, and being at the township level of government, the main link and bond, citizens' general government, itself.
Keywords: Escritórios de projetos; Gerenciamento de projetos; Administração municipal; Gestão pública; Project offices; Project management; Municipal administration; Public management